2008
DOI: 10.1021/jp801408k
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Hollow Vaterite Nanospheres from Amorphous Calcium Carbonate Nanoparticles via Phase Transformation

Abstract: A new and simple method for preparation of hollow calcium carbonate nanospheres under mild conditions is developed. Hollow vaterite nanospheres are achieved by water-induced phase transformation of poly(4-sodium styrene sulfonate)-stabilized amorphous calcium carbonate (PSS−ACC) in water−ethanol solution at room temperature. It is found that the sizes of the resulting hollow-structured nanospheres can be easily regulated by the content of PSS and the phase transformation can be greatly affected by the ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 17 publications
1
69
0
Order By: Relevance
“…In our case, this series of events (i.e., adhesion to the surface followed by breaking away leaving a patch of material on the surface and a hole on the particle) is not present. Cai et al 9 reported the formation of hollow vaterite nanospheres from amorphous calcium carbonate solid particles, controlled by the presence of PSS and water. On applying a much simpler experimental protocol than Cai et al, 9 we did not observe holes in the vaterite particles prepared in the presence of PSS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our case, this series of events (i.e., adhesion to the surface followed by breaking away leaving a patch of material on the surface and a hole on the particle) is not present. Cai et al 9 reported the formation of hollow vaterite nanospheres from amorphous calcium carbonate solid particles, controlled by the presence of PSS and water. On applying a much simpler experimental protocol than Cai et al, 9 we did not observe holes in the vaterite particles prepared in the presence of PSS.…”
Section: Resultsmentioning
confidence: 99%
“…Under such conditions, freshly precipitated calcium carbonate can then be redissolved in a process governed by equilibrium displacement towards the formation of Ca II /PAA complexes at certain points on the particles, eventually resulting in a hole, which will ultimately serve as a release valve for the high concentration of PAA inside the particle. 9 This process is also favored by the osmotic pressure imbalance that evolves from a combination of osmotic flow and concentration changes. This is not observed in the presence of PSS because of its weaker interaction with Ca 2+ cations as compared to PAA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations